Dynamic Oligopoly in the Rice Export Market - Karp, Larry S.; Perloff, Jeffrey M. (The Review of Economics and Statistics, 1989)
A linear-quadratic dynamic oligopoly model is used to estimate the competitiveness of the rice export market. The model nests various market structures using either open-loop or feedback strategies. The estimated feedback model implies a less competitive market structure than the estimated open-loop model. The rice export market is oligopolistic, but it is closer to competitive than collusive. Copyright 1989 by MIT Press.